Establishing the prevalence of common tissue‐specific autoantibodies following severe acute respiratory syndrome coronavirus 2 infection. (13th June 2021) - Richter, Alex G.; Shields, Adrian M.; Karim, Abid; Birch, David; Faustini, Sian E.; Steadman, Lora; Ward, Kerensa; Plant, Timothy; Reynolds, Gary; Veenith, Tonny; Cunningham, Adam F.; Drayson, Mark T.; et al.
Summary: Coronavirus 19 (COVID‐19) has been associated with both transient and persistent systemic symptoms that do not appear to be a direct consequence of viral infection. The generation of autoantibodies has been proposed as a mechanism to explain these symptoms. To understand the prevalence of autoantibodies associated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection,  we investigated the frequency and specificity of clinically relevant autoantibodies in 84 individuals previously infected with SARS‐CoV‐2, suffering from COVID‐19 of varying severity in both the acute and convalescent setting. These were compared with results from 32 individuals who were on the intensive therapy unit (ITU) for non‐COVID reasons. We demonstrate a higher frequency of autoantibodies in the COVID‐19 ITU group compared with non‐COVID‐19 ITU disease control patients and that autoantibodies were also found in the serum 3–5 months post‐COVID‐19 infection. Non‐COVID patients displayed a diverse pattern of autoantibodies; in contrast, the COVID‐19 groups had a more restricted panel of autoantibodies including skin, skeletal muscle and cardiac antibodies. Our results demonstrate that respiratory viral infection with SARS‐CoV‐2 is associated with the detection of a limited profile of tissue‐specific autoantibodies, detectable using routine clinical immunology assays. Further studies are required to determine whether these autoantibodies are specific to SARS‐CoV‐2 or a phenomenon arising from severe viral infections and to determine the clinical significance of these autoantibodies. Abstract : Acute infection with COVID is associated with a pattern of autoantibodies including a high proportion with epidermal antibodies. This autoantibody pattern is more common in severe COVID and is persistent up to 6 months.